2020
DOI: 10.3390/su12198059
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Approach in the Economic Assessment of Interventions for the Reduction of Seismic Vulnerability in Historic Centres

Abstract: The economic evaluation of the interventions aimed at reducing the seismic risk in the historic centres starting from a minimum risk scenario established by law, namely that provided by the Emergency Limit Condition (ELC), and aimed at supporting efficient and effective choices by the public decision-maker pursuing objectives of equity and social well-being, displaying a multidimensional nature. As a result, the evaluation process should integrate more approaches to quantify the different forms of capital invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…For example, if the average WTP for a reduction in mortality due to air pollution in India is INR 10 and there are 100,000 individuals involved, then VSL would be INR 1 million. Besides the WTP approach, VSL can be estimated through the human capital approach, benefits transfer method, and so on. There is a wide range of VSL calculated in the literature, which is as low as INR 4.25 million to the highest INR 56.1 million between the year 1997 and the year 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the average WTP for a reduction in mortality due to air pollution in India is INR 10 and there are 100,000 individuals involved, then VSL would be INR 1 million. Besides the WTP approach, VSL can be estimated through the human capital approach, benefits transfer method, and so on. There is a wide range of VSL calculated in the literature, which is as low as INR 4.25 million to the highest INR 56.1 million between the year 1997 and the year 2019.…”
Section: Methodsmentioning
confidence: 99%
“…For example, if the average WTP for a reduction in mortality due to air pollution in India is INR 10 and there are 100,000 individuals involved, then VSL would be INR 1 million. Besides the WTP approach, VSL can be estimated through the human capital approach, 65 benefits transfer method, 66 Multiobjective Optimization Formulation. In this study, RIES shown in Figure 1 is optimized for three objectives simultaneously.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the aim of investigating the relationships between the "city effect" and the territorial context-both referring to the socio-economic category of capital [136]-a descriptive model organized on two different levels was created, aggregating the elementary indices in two ways:…”
Section: Methodsmentioning
confidence: 99%
“…The data collection form was used to collect data, consisting of two parts: the first part collected demographic data of the patients and the second section collected information about the costs of physician visits, heart medications, BNP test, diagnostic and laboratory services, hospitalization and rehospitalization, nursing, special equipment, private service, accommodation and traveling. The costs of productivity loss due to heart failure were estimated by employing the human capital approach [ 30 ].…”
Section: Methodsmentioning
confidence: 99%